Extraterrestrial Intelligent Life and Christology at Teilhard de Chardin - Udías Vallina, Agustín (Razón y fe, 2020)
The existence of other habitable worlds has been proposed from antiquity and from the Copernican revolution, a plurality of worlds have been considered. The present image of the universe, with thousands of millions of galaxies and in them thousands of millions of stars around which there are planetary systems, makes very probable the existence of extraterrestrial intelligent life, although there is not yet clear evidence of it. Christian theology does not deny this possibility and proposes several ways of understanding sin, grace, redemption and incarnation in an inhabited universe. Teilhard de Chardin considers the problem and relates in each case its situation with life evolution according the law of complexity- consciousness, and its final realization in the union in the Christ-Omega. He proposes a multiplicity of incarnations of the Cosmic-Christ, without totally excluding the possibility of only one in the earth valid for the whole universe.